Tuturan Ritual Natoni Adat Masyarakat Etnis Timor dalam Penyambutan Tamu di Sekolah (Universitas Negeri Semarang, 2016)
Tujuan penelitian ini adalah untuk mendeskripsikan dan menjelaskan bentuk kebahasaaan tuturan ritual natoni adat masyarakat etnis Timor, fungsi kebahasaan tuturan ritual natoni adat masyarakat etnis Timor dan makna budaya kebahasaan tuturan ritual natoni adat masyarakat etnis Timor. Pendekatan dalam penelitian ini menggunakan pendekatan teori lingusistik kebudayaan. Teknik pengumpulan datamenggunakanteknik simak dan wawancara. Teknik analisis data dilakukan dengan menggunakan model interaktif dielektif. Hasil penelitian ditemukan berbagai bentuk kebahasaan, mencakup : bentuk kata, bentuk frasa, bentuk kalimat, bentuk wacana; fungsi kebahasaan, mencakup: fungsi informasional, fungsi ekspresif, fungsi direktif, fungsi estetis, fungsi fatik; dan makna budaya kebahasaan yang terdapat dalam tuturan ritual natoni adat masyarakat etnis Timor dalam penyambutan tamu di sekolah.The purpose of this study is to describe and explain the ritual forms of speech kebahasaaan natoni Timor indigenous ethnic communities, linguistic utterances ritual function natoni etnis Timor indigenous communities and the cultural meaning of linguistic utterances natoni ritual indigenous ethnic communities Timor. The approach in this study using the approach of linguistic theory of culture. Data collection technique used see and interview techniques. In doing techniques refer, applied recording technique as the basic technique. Then proceed with the advanced technique in the form of free refer techniques involved capably, recording technique, and the technique of record. Furthermore, the technique of structured and unstructured interviews. Mechanical analysis of data using interactive models dielektif. The research found various forms of language, include: word a form, phrase form, form of sentences, form discourses, linguistic functions, include: informational function, expressive function, directive function, aesthetic function, phatic function; linguistic and cultural meaning contained in ritual speech natoni indigenous ethnic communities in welcoming guests at the school.